Sistema de auxílio visual do reposicionamento ósseo por meio da cirurgia ortognática - Morais, Giuliano Diniz de (2013)
The use of computer graphics technology, applied in different areas of health is certainly notable, having positive and reliable results, thus pushing for innovative techniques. The current literature still lacks of collateral to support surgeons and their patients on the orthognathic surgery field. Orthognatic Surgery usually is applicable to patients who have used traditional braces, and did not obtain satisfactory results. The Orthognatic Surgey provides a manner to do a jaws breakdown through a controlled set of procedures with certain security levels. It is through surgical procedure that a perfect dental occlusion is expected. It is important to note that patients suitable for this procedure should have very pronounced symptoms, with origin in the relation between the teeth, muscles and bones. These problems may cause a set of symptoms, among them are pain in the face, incorrect tongue and TMJ positioning, headaches and stomach disorders ( due to improper chewing) , respiration and phonation issues. This paper describes a 3D analysis and simulation of a procedure for orthognathic surgery, with the goal of providing a better assistance for surgical planning using CT scans efficiently. There is also a motivation to include the software code written in this dissertation as part of the InVesaliusTM system, from CTI, in order to leverage the capabilities of orthognatic surgery planning and simulation and its expected outcomes.